Um estudo da gestão financeira das micro e pequenas empresas comerciais do município de Carapicuíba - Lopes, José Eduardo Ferreira (2011)
Studies have shown that there are major obstacles for Micro and Small Enterprises remain on the market for long periods of time due to many restrictive factors for its permanence. In this study we intend to analyze how accounting is being used for important decisions to ensure the survival and growth of these companies. The methodology used was the exploratory study of cross-section through a form with thirteen questions answered by thirty commercial companies located in the city of Carapicuíba. It was concluded that although the companies have improved in many aspects that have increased the length of its surviving, the use of accounting information in decision-making is still in its primary stage, with its centralizing, planning and control in the person of the owner of the company by means of barely structured information